Multilingual modal sense classification using a convolutional neural network [Source code] - Marasović, Ana (Universität, 2019)
Abstract Modal sense classification (MSC) is aspecial WSD task that depends on themeaning of the proposition in the modal’s scope. We explore a CNN...